Synthesis and investigation of neptunium zirconium phosphate, a member of the NZP family: crystal structure, thermal behaviour and Mössbauer spectroscopy studies. Issue 35 (23rd August 2017) - Bykov, D. M.; Konings, R. J. M.; Apostolidis, C.; Hen, A.; Colineau, E.; Wiss, T.; Raison, P.
Abstract : We synthesized a new NZP-type neptunium zirconium phosphate Np0.29 Zr2 (PO4 )3 and investigated it by Rietveld analysis, infrared spectroscopy and Mössbauer spectroscopy. Abstract : A new double neptunium zirconium phosphate of the type M x Zr2 (PO4 )3 (M = Np), crystallizing in the structure type NaZr2 (PO4 )3 (NZP, NASICON), was synthesized by solid state reactions at high temperatures and characterized by X-ray diffraction, infrared spectroscopy and Mössbauer spectroscopy. The Rietveld refinement of the XRD pattern together with the analysis of the IR spectra of the sample confirmed the space group P 3̄ c, the same as that for the lanthanide analogues Ln0.33 Zr2 (PO4 )3 . However, Mössbauer studies revealed the presence of neptunium in the two oxidation states +3 and +4, indicating a two-phase NZP system with different crystallographic environments of the neptunium atoms. The thermal behaviour of the sample was followed up to 1400 °C by thermogravimetric analysis.